A study on damages under the tort of defamation and possible guidelines in assessing the quantum of damages: a comparative study with Ireland / Mohd Syazwan Ramli, Mohd Hafiz Haja Najmuddeen and Wafri Adi Mohamad Yusof - Ramli, Mohd Syazwan; Najmuddeen, Mohd Hafiz Haja; Yusof, Wafri Adi Mohamad (2011)
Modernization has caused the immense social changes where people nowadays prefer to use emails to communicate with one another. This can be seen in which people are able to express freely their thoughts and thinking without considering the consequences of the statement made. This is where the defamation law come into picture to restrain or punish anyone who commits the offence. So, remember talking trash online does not mean you would not get caught. The purpose of this study is to propose the comprehensive guidelines for assessing the quantum of award in defamation suits in Malaysia. Apart from that, a comparison has been made between the same laws of our country with another country on matter regarding to the procedures and guidelines in awarding damages. In conclusion, we also will examine the implementation of the existing laws and guidelines (if any) in Malaysia as well as in Ireland.